KAN VE KAN ÜRÜNLERİYLE BULAŞAN İNFEKSİYONLAR: RUTİN TARAMA TESTLERİ VE MOLEKÜLER TANI YÖNTEMLERİ - Kocazeybek, Bekir (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Identification of agents transmitted by the transfusion of blood and blood products and developments in screen tests for these infections made the transfusion security contemporary, and especially by the effect of AIDS, public attention went towards to the infections transmitted by transfusion in all countries. Further improvements in routine present screen tests decreased especially the transmission risk of virus infections transmitted by the transfusion of blood and blood products. Transmission risk of virus infections is not zero against all improvements, in these days the strategy of blood banks has to reach to the zero risk. Molecular techniques were applied to the studies of blood banks in order to decrease the window period to reach an available shortest time for the security of donor bloods. HCV-NAT test is obligatory for the plasma products especially in Europe but the routine use of molecular techniques related with other factors is debatable. Further studies are needed in order to solve problems specific to the molecular techniques. Primary approach, in order to prevent the transmitting infections by transfusion of blood and blood products and to supply the uninfected blood with the lowest risk, is depended on performing present screen tests with a high quality standard and these screen tests has to include all blood donations. National quality control network has to set up for this purpose. Otherwise; well-known problems will go on and the real dimensions of problems will not known. The desire of applying new technologies to the routine works and populist and unrealistic approaches will cost money and cause wastefulness of resources in countries having limited resources like our country.